2020
DOI: 10.3389/fphar.2020.00973
|View full text |Cite
|
Sign up to set email alerts
|

ABCB1 Genetic Variants as Predictors of Irinotecan-Induced Severe Gastrointestinal Toxicity in Metastatic Colorectal Cancer Patients

Abstract: Irinotecan is widely used in the treatment of metastatic colorectal cancer (mCRC) despite its severe toxicities. Toxicity is often associated with the UGT1A1*28/*28 genotype. An explanation for idiopathic toxicity beyond the UGT1A1 biomarker, however, remains a major concern for clinicians. One of the main irinotecan transporters is P-glycoprotein (Pgp), which is a hepatic efflux pump encoded by ABCB1. P-gp is involved in the biliary excretion of irinotecan and its active metabolite SN-38. We aimed to assess w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 30 publications
(45 reference statements)
2
18
0
Order By: Relevance
“…In literature, administration of strong inhibitors of CYP3A4 such as azoles or diltiazem increases sirolimus trough concentrations [ 21 ], as does the co-administration of cyclosporine, a substrate and inhibitor of the p-glycoprotein [ 33 ]. In our study, irinotecan, a p-glycoprotein substrate that may compete for p-glycoprotein transport [ 32 , 34 ], was administered during a 90 min infusion in different doses (125, 200, or 240 mg/m 2 ) just prior to sirolimus intake on D1. No effect of irinotecan doses was observed on sirolimus pharmacokinetic parameters ( p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…In literature, administration of strong inhibitors of CYP3A4 such as azoles or diltiazem increases sirolimus trough concentrations [ 21 ], as does the co-administration of cyclosporine, a substrate and inhibitor of the p-glycoprotein [ 33 ]. In our study, irinotecan, a p-glycoprotein substrate that may compete for p-glycoprotein transport [ 32 , 34 ], was administered during a 90 min infusion in different doses (125, 200, or 240 mg/m 2 ) just prior to sirolimus intake on D1. No effect of irinotecan doses was observed on sirolimus pharmacokinetic parameters ( p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with colorectal cancer, rs2032582 GG genotype correlates with the highest P- glycoprotein expression in the tumor tissue [ 46 ]. In accordance with the ABCB1 expression, its rs2032582 polymorphism was associated with irinotecan-induced severe mucositis in metastatic colorectal cancer patients [ 47 ]. CD36 is a multi-ligand scavenger receptor whose primary function is to take up fatty acids and oxidized lipoproteins into cells [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from metabolizing enzymes, polymorphisms within transport proteins may also affect the efficacy of irinotecan. The increased expression of ATP-binding cassette subfamily B member 1 (ABCB1, P-glycoprotein (P-gp)) participating in the biliary excretion of CPT-11 and SN-38 has been found to raise SN-38 secretion, which results in its diminished plasma levels and an enhanced risk of intestinal toxicity, decreasing at the same time the risk of neutropenia [ 93 , 94 , 95 ]. Several ABCB1 variants—including rs1128503 (1236 C/T), rs2032582 (2677 G>T/A), and rs1045642 (3435 C/T)—have been confirmed to affect P-gp expression, SN-38 plasma concentrations, and renal clearance [ 96 , 97 ].…”
Section: The Impact Of Genetic Variations On Anticancer Treatment Eff...mentioning
confidence: 99%
“…Several ABCB1 variants—including rs1128503 (1236 C/T), rs2032582 (2677 G>T/A), and rs1045642 (3435 C/T)—have been confirmed to affect P-gp expression, SN-38 plasma concentrations, and renal clearance [ 96 , 97 ]. Riera et al [ 93 ] suggested the ABCB1 rs1128503 variant as a predictor of irinotecan-related severe gastrointestinal toxicity, especially diarrhea and mucositis. Moreover, the rs2032582 variant also seems to increase the risk of severe mucositis.…”
Section: The Impact Of Genetic Variations On Anticancer Treatment Eff...mentioning
confidence: 99%